1998
DOI: 10.1021/js980109t
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion complexation of ziprasidone mesylate with β-cyclodextrin sulfobutyl ether

Abstract: Ziprasidone is an antipsychotic agent indicated primarily for the treatment of schizophrenia. An intramuscular dosage form of ziprasidone was developed using beta-cyclodextrin sulfobutyl ether (SBECD) to solubilize the drug by complexation. Inclusion complexation of ziprasidone mesylate (ZM) with SBECD was studied by circular dichroism (CD) spectroscopy, proton nuclear magnetic resonance (1H NMR) spectroscopy, Monte Carlo simulations, phase-solubility studies, and counterion titration. The results of the studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 24 publications
1
46
0
1
Order By: Relevance
“…48 Kim et al 49 also reported on a combination of salt formation and formulation strategies to enhance the solubility of a drug for parenteral dosage forms. The mesylate salt of ziprasadone had an intrinsic solubility of 0.89 mg/mL; however, this was inadequate to achieve the required solubilities for intramuscular administration (20-40 mg/mL).…”
Section: Solubility/dissolution Advantagesmentioning
confidence: 99%
“…48 Kim et al 49 also reported on a combination of salt formation and formulation strategies to enhance the solubility of a drug for parenteral dosage forms. The mesylate salt of ziprasadone had an intrinsic solubility of 0.89 mg/mL; however, this was inadequate to achieve the required solubilities for intramuscular administration (20-40 mg/mL).…”
Section: Solubility/dissolution Advantagesmentioning
confidence: 99%
“…Ziprasidone mesylate was supplied as 30 mg sterile lyophilized powder in a 10 ml clear, glass vial. This was reconstituted with 1.2 ml sterile water, producing a 1.5 ml stock solution containing 20 mg/ml ziprasidone mesylate and 294 mg/ml of the cyclodextrin derivative, sulphobutylether betacyclodextin (SBECD), a novel excipient that enhances the solubility of ziprasidone (Kim et al 1998). The 20 mg dose was prepared by drawing 1 ml of the stock solution, and the 2 mg dose was prepared by adding 0.03 ml of the stock solution to 0.97 ml of a separately prepared SBECD solution.…”
Section: Study Design and Treatmentmentioning
confidence: 99%
“…The development of an IM formulation of ziprasidone, using sulfobutylether beta-cyclodextrin to solubilize the drug by forming a complex (Kim et al 1998), provides a means of administering ziprasidone to patients for whom an IM formulation is the preferred route because of acute symptoms of agitation associated with psychosis. Ziprasidone IM attains peak exposure within approximately 30 min, exposure is dose-related and there is negligible drug accumulation with multiple dosing (Miceli et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced dissolution may be due to inclusion complex Ziprasidone in Treating Schizophrenia formation as well as raised mechanistic impinging during dissolution [60,61]. The in vitro dissolution studies of solid dispersion by spray drying with Kollidon, F-127 in 7.2 po4 buffer with 92.05%, and 73.3% drug being released within 20 min, Whereas in case of Soluplus almost 92.97%,drug was released in 20 min in 7.2 po4 buffer.…”
Section: In Vitro Dissolutionmentioning
confidence: 99%
“…The literature data indicate that many studies are carried out for solubility enhancement of Ziprasidone focussing on utilization of various derivatives of cylodextrins [40,41]. It has been shown that different salt forms of Ziprasidone have different solubility due to the degree of ion pair formation between ziprasidone & the counterion [42].…”
Section: Introductionmentioning
confidence: 99%